Collaborative defending scheme against malicious Web pages based on social trust - Xin LIU; Chun-fu JIA; Guo-you LIU; Zhi-chao HU; Dong WANG (Tongxin xuebao)
To deal with the threat of malicious Web pages,a distributed defending scheme against malicious Web pages based on social trust was proposed.Besides the malicious URL list from third-party professional organizations,the direct and indirect trust relations between friends in social network were used to obtain evaluations of Web pages.The experiences about Web surfing from a user’s friends were collected to result in synthetical evaluations on his computer.Each user cooperated with his friends,so that a defending system was formed on the overall perspective,which can improve the defending ability of the social network against malicious Web pages.The experiment results indicate that the visits of malicious Web pages under the scheme decrease obviously than the methods without social trust.